Inovasi Alat Pemisah Daun Kelapa dan Modul Penjualan Online untuk Meningkatkan Pendapatan dari Sapu Lidi di Desa Karang Rejo - Muhammad Fatwa Sukmawan; Ceysha Diva Ratu Pramudya; Riko Endrizal; Rihadatul Aisy; Meilani Audi Kustanti; Tiara Devina Putri (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service Program aimed to enhance the productivity of broomstick craftsmen in Karang Rejo Village by innovating a coconut leaf separator tool and developing an online sales module. Traditionally, the separation process was manual, labor-intensive, and time-consuming, limiting production and income. The team designed a simple yet effective tool that increased daily output from 1–5 bundles to 6–7 bundles. Additionally, a digital sales module using platforms like Shopee was introduced to expand market reach. As a result, the local community improved production efficiency and gained new knowledge in modern marketing strategies. This program not only empowers the community economically and technologically but also promotes environmental sustainability by utilizing coconut leaves as economic resources. By applying appropriate technology and a digital approach, this initiative serves as a replicable model of village empowerment through local innovation, contributing to long-term economic growth and ecological awareness in rural areas.